2020
DOI: 10.1155/2020/5609623
|View full text |Cite
|
Sign up to set email alerts
|

Establish a Scoring Model for High-Risk Population of Gastric Cancer and Study on the Pattern of Opportunistic Screening

Abstract: Objective. To investigate and study the related risk factors of gastric cancer (GC) patients, to establish a high-risk scoring model of GC by multiple logistic regression analysis, and to explore the establishment of a GC screening mode with clinical opportunistic screening as the main method, and by using the pattern of opportunistic screening to establish the screening of high-risk GC patients and the choice of screening methods in the clinical outpatient work. Methods. Collected the epidemiological question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…We all know that GC is strongly associated with gene expression, Hp infection, lifestyle, and so on 18 . Consistent with a previous study, 19 age and high salt diet showed differences between the GC and NGC groups. It has been concluded that long‐term excessive salt intake may enhance the carcinogenic pathway by inducing Hp proliferation and colonization and that preserved vegetables often contain excessive amounts of nitrate and nitrite carcinogens in addition to high salt content, which together form nitroso complexes with irreversible effects on the cellular activity cycle 20…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We all know that GC is strongly associated with gene expression, Hp infection, lifestyle, and so on 18 . Consistent with a previous study, 19 age and high salt diet showed differences between the GC and NGC groups. It has been concluded that long‐term excessive salt intake may enhance the carcinogenic pathway by inducing Hp proliferation and colonization and that preserved vegetables often contain excessive amounts of nitrate and nitrite carcinogens in addition to high salt content, which together form nitroso complexes with irreversible effects on the cellular activity cycle 20…”
Section: Discussionsupporting
confidence: 90%
“…This study followed the ethical principles of medical research involving human subjects in the Declaration of Helsinki and was approved by the ethics committee of our hospital (Quick-PJ-2022- [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“… 13 14 Such opportunistic screening is performed on a voluntary basis, based on an individual or physician’s request. 14 The screening rate for HP in China (21.7%) is far from satisfactory, 15 and the general population’s lack of awareness of HP risk factors or symptoms and negative attitude towards screening contribute to delays in diagnosis. 11 …”
Section: Introductionmentioning
confidence: 99%
“…However, although eradication of HP to prevent GC has a cost–benefit advantage,10 China lacks national policies or protocols for HP in GC screening 11. HP infection is usually asymptomatic,12 and China has a large population and relatively poor medical and health resources; therefore, opportunistic screening of asymptomatic people is currently the main approach 13 14. Such opportunistic screening is performed on a voluntary basis, based on an individual or physician’s request 14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation